Three-dimensional facial swelling evaluation of piezo-electric vs conventional drilling bur surgery of impacted lower third molar: a randomized clinical trial - A. Caputo; E. Rubino; A. Marcianò; M. Peditto; A. M. Bellocchio; R. Nucera; G. Oteri (BMC, 2023)
Abstract Background Among the post-surgical complications of lower wisdom teeth surgery, swelling is considered by patients one of the most impairing, with both social and biological influences and impacting patients' quality of life. Aim of the study was to evaluate the swelling following the osteotomy when performed with drilling burs versus piezo-electric instruments in the mandibular impacted third molar extraction, using a facial reconstruction software. Materials and methods A randomized, split-mouth, single-blind study was conducted on patients, ranging between 18 and 40 years of age, requiring lower third molars extraction and referred at the Oral Surgery Unit of the School of Dentistry of the University of Messina. Twenty-two patients were recruited during an 8 months period according to the following criteria: good general health conditions; bilateral, symmetrical, impacted third molars; no use of medication that would influence or alter wound healing; no temporomandibular joint disorder history; no smoking. All patients underwent bilateral surgical removal. For each patient, a facial scan was obtained prior to the surgical procedures. The two extractions were conducted performing, in a randomized way, osteotomy with rotatory burs or use of piezo surgical instruments. Facial scans were repeated at 3 and 7 days after the surgical procedures. Volumetric differences were calculated via superimposition using a dedicated software. The data obtained were processed using paired t-test. Results The results obtained from our study showed no significant differences between two groups regarding post-operative swelling. To the best of our knowledge, this study represents the first experience of using an objective method that can be reproducible on the collection of patients' clinical parameters. Conclusions The 3D digital analysis, in the evaluation of facial swelling, is a technique of simple application, objective, reproducible, reliable, decreasing the variables of error. Based on these data, it is possible to conclude that piezo surgery is a safe way for performing the osteotomies during third molar surgery. However, regarding the post-operative swelling, it does not show an advantage over classical rotary instruments. Trial registration Registered on ClinicalTrials.gov (ID: NCT05488028, on 04/08/2022). Approved by Ethical Committee of Messina: (ID 01-2020, on 27/04/2020).